Queering desire
1 online resource.
Keywords: "Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women's and non-binary people's experiences of identity and desire. Taking an intersectional feminist approach and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing and eroticism have often neglected AFAB, transfeminine and non-binary people's experiences. Through twenty-five newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, and history. history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention"--